Considering the relationship between sleep and empathy and compassion in mental health nurses: It's time. (14th May 2020) - Gerace, Adam; Rigney, Gabrielle
Abstract: Sleep plays a critical role in overall health, well‐being, and daytime functioning. Provision of 24‐hour care means that nurses undertake shift work and therefore have been found to commonly not get the recommended amount of sleep, resulting in sleep deprivation. Research to date has focused on how sleep deprivation impacts their cognitive performance (e.g., reaction time, memory consolidation); however, less considered is how nurses' sleep impacts on their ability to understand and provide emotional care to consumers. In this paper, we examine how sleep may influence nurses' ability to empathize and provide compassionate care, both of which are fundamental aspects of their work. We begin by considering the unique challenges nurses face as shift workers and the impact of sleep on physical and psychological functioning. We examine how empathy and compassion drive nurses' attempts to understand consumers' perspectives and experiences and motivate them to want to help those in their care. Work directly investigating the relationship between sleep and these processes indicates emotional recognition and experience are hampered by poor sleep, with greater compassion towards oneself or from others associated with better sleep. Much of this work has, however, been conducted outside of the nursing or health professional space. We discuss issues that need to be addressed in order to move understanding forward regarding how sleep impacts on mental health nurses' empathy and compassion, as well as how an understanding of the sleep–empathy/compassion link should be an important priority for nurse education and well‐being.